Pulmonary mucoepidermoid carcinoma in the Chinese population: A clinical characteristic and prognostic analysis - Li, Qiuyu; Wei, Xuejing; Wang, Yanfei; Liu, Chang; Fan, Boshi; Lv, Cheng; Si, Wenzhe; Li, Min (Frontiers in Oncology, 2022)
Background Mucoepidermoid carcinoma is dominant in salivary glands and rarely occurs in the lung. Primary pulmonary mucoepidermoid carcinoma is a type of non-small-cell lung cancer, but the prognostic factors in Chinese patients remain controversial. This investigation aimed to review cases of pulmonary mucoepidermoid carcinoma, analyse the prognosis of this disease and discuss treatment strategies. Methods Patients with pathologically proven pulmonary mucoepidermoid carcinoma were screened at the Department of Respiratory and Critical Care Medicine at the Peking University Third Hospital, Beijing Friendship Hospital Affiliated to Capital Medical University, and Peking University Cancer Hospital for inclusion in this retrospective study. Demographic data, including age, sex, clinical symptoms, smoking, alcohol consumption, allergies, family history, imaging findings, fibrobronchoscopy findings, surgical procedures, tumour location and pathologic stage, were collected. Telephone follow-up was conducted for all patients not lost to follow-up. The associations of sex, age, smoking, tumour differentiation, tumour size, lymph node metastasis, pathologic stage, and patient survival were retrospectively analysed. Kaplan–Meier, univariate and multivariate analysis curves were used to analyse patient prognosis and prognostic factors. Results Thirty-one patients, comprising 23 males and 8 females, were enrolled in the analysis. The mean age was 60.77 ± 11.44 years. The first symptom was nonspecific, with cough being the most common (21/31, 67.77%); smokers accounted for 17 of the 31 patients, and ten patients had a history of alcohol consumption. In our Cox univariate survival analysis of patients with pulmonary mucoepidermoid carcinoma, we found that TNM stage IV, degree of differentiation and lymph node metastasis were risk factors for pulmonary mucoepidermoid carcinoma and that degree of differentiation was an independent risk factor. Conclusion The clinical, radiographical and pathological features of pulmonary mucoepidermoid carcinoma were systemically analysed and summarized, and the degree of differentiation and lymph node metastasis, as well as prognostic factors in addition to clinical stage, were confirmed.